Case reports of juvenile GM1 gangliosidosisis type II caused by mutation in GLB1 gene - Parvaneh Karimzadeh; Samaneh Naderi; Farzaneh Modarresi; Hassan Dastsooz; Hamid Nemati; Tayebeh Farokhashtiani; Bibi Shahin Shamsian; Soroor Inaloo; Mohammad Ali Faghihi (BMC, 2017)
Abstract Background Type II or juvenile GM1-gangliosidosis is an autosomal recessive lysosomal storage disorder, which is clinically distinct from infantile form of the disease by the lack of characteristic cherry-red spot and hepatosplenomegaly. The disease is characterized by slowly progressive neurodegeneration and mild skeletal changes. Due to the later age of onset and uncharacteristic presentation, diagnosis is frequently puzzled with other ataxic and purely neurological disorders. Up to now, 3-4 types of GM1-gangliosidosis have been reported and among them type I is the most common phenotype with the age of onset around 6 months. Various forms of GM1-gangliosidosis are caused by GLB1 gene mutations but severity of the disease and age of onset are directly related to the position and the nature of deleterious mutations. However, due to its unique genetic cause and overlapping clinical features, some researchers believe that GM1 gangliosidosis represents an overlapped disease spectrum instead of four distinct types. Case presentation Here, we report a less frequent type of autosomal recessive GM1 gangliosidosis with perplexing clinical presentation in three families in the southwest part of Iran, who are unrelated but all from "Lurs" ethnic background. To identify disease-causing mutations, Whole Exome Sequencing (WES) utilizing next generation sequencing was performed. Four patients from three families were investigated with the age of onset around 3 years old. Clinical presentations were ataxia, gate disturbances and dystonia leading to wheelchair-dependent disability, regression of intellectual abilities, and general developmental regression. They all were born in consanguineous families with no previous documented similar disease in their parents. A homozygote missense mutation in GLB1 gene (c. 601 G > A, p.R201C) was found in all patients. Using Sanger sequencing this identified mutation was confirmed in the proband, their parents, grandparents, and extended family members, confirming its autosomal recessive pattern of inheritance. Conclusions Our study identified a rare pathogenic missense mutation in GLB1 gene in patients with complex neurodevelopmental findings, which can extend the list of differential diagnoses for childhood ataxia in Iranian patients.